Suitability Of Visual Communication Content On Instagram Against Ministry Of Religion Religious Moderation Concept - Zikrillah, Abdu; Mutaqin, Zaenal (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2024)
This research discusses the suitability of content through visual communication on Instagram social media to the concept of religious moderation. In the dynamics of da’wah using online digital media such as Instagram, several problems have been discovered, one of them is da’wah content which is considered less moderate. Problems occur due to various differences in viewpoints, mazhab, and understanding regarding da’wah material. The delivery of the da’wah material is considered to conflict with the ministry of religion's concept of religious moderation. The aim of this research is to see and discuss the suitability of da’wah content on Instagram to the concept of religious moderation. The research method uses content analysis and semiotics to understand the message in da’wah content on Instagram, then analyzed based on the concept of religious moderation from the ministry of religion. The results of the discussion showed that some content was considered less than moderate due to several factors, namely the lack of explanation in the description or caption section, which could lead to misunderstanding of the meaning and intent of conveying content on Instagram. Apart from that, visualization in the form of illustrations and symbols can provide different interpretations of the understanding received by mad'u, because not all mad'u, especially Instagram users, can understand the message according to what the Da’i conveys.